Hearing Loss due to Infiltration of the Tympanic Membrane by Chronic Lymphocytic Leukemia - Jonathon B. Cohen; Robert Cavaliere; John C. Byrd; Leslie A. Andritsos (Case Reports in Hematology)
Central nervous system (CNS) involvement by chronic lymphocytic leukemia (CLL) can present with dramatic neurologic findings or can be quite subtle, discovered only at the time of autopsy. We describe a case of CLL in a patient who presented initially with hearing loss and was ultimately found to have involvement of the tympanic membrane. She noted improvement of her hearing after induction therapy but was not aware at the time of the involvement of her CNS with CLL. Upon worsening of hearing at the time of relapse, she was evaluated by imaging and CSF analysis as well as biopsy of the tympanic membrane, and involvement of the CNS was confirmed. She has received CNS-directed therapy with intrathecal liposomal cytarabine and intravenous CNS-directed therapy and has noted improved hearing and resolution of her imaging and CSF findings. This is the first reported case of tympanic membrane involvement with CLL and describes potentially effective methods for managing this challenging complication.